The Epistemology of Al-Maqosidi's Interpretation in the Holy Qur'an: An Analytical Study of Rasā’il al-Nūr by Bedi'uzzaman Said An-Nursi: نظرية المعرفة في التفسير المقاصدي للقرآن الكريم:دراسة تحليلية في رسائل النور لبديع الزمان سعيد النورسي - Achmad Ilham Maulana; Nurul Ani Safitri (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, Cianjur, indonesia, 2025)
This study aims to analyze the epistemological foundations of maqāṣid-based Qur'anic interpretation in the work of Bediuzzaman Said Nursi, particularly through his Risālah al-Nūr corpus. Employing a qualitative descriptive-critical method, the study investigates the textual discourse of Nursi to extract the underlying epistemology in his construction of Qur’anic objectives (maqāṣid). The findings show that Nursi’s approach goes beyond presenting maqāṣid as mere legal aims; rather, he builds them upon fitrah (innate human disposition), revelation, and reason, viewing them as internal structures of the Qur’anic text. The research focuses on four central objectives in Nursi’s framework: Tawḥīd (Divine Unity), Prophethood, Resurrection, and Justice. The novelty of this research lies in its epistemological reading of Nursi’s tafsir and in highlighting his contribution to contemporary renewal in Qur'anic interpretation.